2017
DOI: 10.3727/096368916x693473
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell-Conditioned Medium Suppresses Inflammation and Promotes Spinal Cord Injury Recovery

Abstract: Spinal cord injury (SCI) causes functional impairment as a result of the initial injury followed by secondary injury mechanism. SCI provokes an inflammatory response that causes secondary tissue damage and neurodegeneration. While the use of neural stem cell (NSC) engraftment to mitigate secondary injury has been of interest to many researchers, it still faces several limitations. As such, we investigated if NSC-conditioned medium (NSC-M) possesses therapeutic potential for the treatment of SCI. It has been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…Only 28 articles reported sufficient data to perform a statistical test, including subgroup evaluation ( Fig. 1 ) [ 2 3 4 5 6 7 14 15 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]. Besides effect size preparation from these 28 studies, other useful data such as the most popular model, the location of injuries and types of stem cell also extracted from the articles and they are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Only 28 articles reported sufficient data to perform a statistical test, including subgroup evaluation ( Fig. 1 ) [ 2 3 4 5 6 7 14 15 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]. Besides effect size preparation from these 28 studies, other useful data such as the most popular model, the location of injuries and types of stem cell also extracted from the articles and they are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the micro-environmental cytotoxicity caused by acute SCI presents considerable obstacles against cellular engraftment [22]. Furthermore, some treatments come with important concerns, including painful responses to nonpainful stimuli after neural stem cell transplantation, ethical concerns, or the formation of teratomas after embryonic stem cell therapy [8]. Hosseini et al [12] reported that BMSCs can differentiate into neural stem cells and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that less than 1% of MSCs survive for more than 1 week after systemic administration [16]. Loss of differentiation potential, initiation of the host immune response, difficulties in delivery, and poor engraftment of transplanted cells are the major limitations of cell-based therapies [8,24]. Since the main effects of MSCs are likely mediated by paracrine mechanisms [25], we examined the effect of BMSC-CM as an alternative treatment for SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, beside surgical intervention, the common approach to treat SCI is applied large doses of steroids, such as methylprednisolone. However, this treatment has been largely discontinued due to its time sensitivity and the severe side effects [34]. A growing body of evidence indicate that BMSCs can ameliorate motor functions in animal models of SCI by regulating diverse pathophysiological events including oxidative stress, apoptosis and in ammatory reactions [35].…”
Section: Discussionmentioning
confidence: 99%